The Level of Use of Antibiotics as Self-medication in Taman Bumyara Housing, Mustikajaya District Bekasi - Alisa Dewi Nurmitasari; Lilian Batubara (Junior Medical Journal, 2022)
Background: Antibiotics are drugs that used to treat bacterial infections. Irrational use of antibiotics can lead to resistance. The use of antibiotics must be through a doctor’s prescription because use without a prescription is very likely to couse irrational use. Using of antibiotics Inappropriate self-medication is one of the causes of antibiotic resistance. The purpose of this study was to determine the level of use of antibiotics as self-medication in Taman Bumyagara Housing, Mustikajaya District.Method: The type of research used is descriptive observational with a cross sectional research design. The sample in this study amounted to 140 people. The data used are primary data using a google form questionnaire and analyzed by univariate analysis presented in tabular and narrative form.Result: Based on the research that has been done, the results of measuring the level of antibiotic use, respondents had a level of infrequent use (89.3%). For the types and preparations of drugs for self-medication, 94.3% of respondents used Amoxicillin and 94.3% who chose tablets. Based on the indications for use, there are 77.9% of respondents using antibiotics for fever. Profile of self-medication use of antibiotics, respondents using drugs orally (100%) with frequency of use (98.6%), interval of use (97.9%), dose of use (97.9%) according to the brochure, and duration of use was not according to needs (32.9%).Conclusion: The use of antibiotics as self-medication in Taman Bumyagara Housing, Mustikajaya District is low level.